Study on Gradation and Performance of Cold Patch Asphalt Mixtures. Issue 1 (October 2020) - Qiang, Li; Feiyi, Liu; Xiao, Luo; Fan, Shen
Abstract: In this paper, SMA-13 and LB-13 gradations are designed in order to study the influence of cold patch asphalt mixture gradation and the component changes of cold patch asphalt liquid on the performance of cold patch asphalt mixture. By measuring the volume parameters and Marshall stability of the two asphalt mixtures, the gradations are compared and analyzed. By measuring the Marshall stability and residual stability of LB-13 cold patch asphalt mixture with different anti stripping agent content, asphalt to diesel ratio and cold patch agent content, the influence of the component changes of cold patch asphalt liquid on the Marshall performance and water stability of the mixture was studied. It is found that the Marshall stability of LB-13 asphalt mixtures is slightly lower than that of SMA-13 asphalt mixtures, and the void ratio is 13.4%, which is conducive to diesel volatilization. Compared with SMA-13 gradation, LB-13 asphalt mixture is more suitable as the reference gradation of cold patch asphalt mixture. When the content of anti stripping agent is 0.30 % ∼ 0.40 %, the Marshall stability of cold patch asphalt mixture increases gradually with the increase of anti stripping agent content, while the immersion residual stability increases first and then decreases with the increase of anti stripping agent content, and the immersion residual stability reaches the highest value (89.2 %) when the content of anti stripping agent is 0.35 %. When the ratio of asphalt to diesel is 74:24 ∼ 82:16, the residual stability of cold patch asphalt mixture increases with the increase of the ratio of asphalt to diesel, and when the ratio of asphalt to diesel is more than 80:14, the Marshall stability of cold patch asphalt mixture increases significantly, which is higher than 7 kN. The Marshall stability of cold patch asphalt mixture decreases with the increase of cold patch agent when the content of cold patch agent is 1.7 % ∼ 2.3 %; the immersion residual stability decreases first and then increases with the increase of cold patch agent, and reaches the highest when the content of cold patch agent is 1.7 %, which is 89.6 %. Considering the Marshall performance and water stability of cold patch asphalt mixture, when the ratio of asphalt to diesel oil is 78:20, the content of cold patch agent is 1.7 %, and the content of anti stripping agent is 0.35 %, the performance of cold patch asphalt mixture is the best.